2007
DOI: 10.1371/journal.ppat.0030104
|View full text |Cite
|
Sign up to set email alerts
|

Regulated Degradation of the HIV-1 Vpu Protein through a βTrCP-Independent Pathway Limits the Release of Viral Particles

Abstract: Viral protein U (Vpu) of HIV-1 has two known functions in replication of the virus: degradation of its cellular receptor CD4 and enhancement of viral particle release. Vpu binds CD4 and simultaneously recruits the βTrCP subunit of the SCFβTrCP ubiquitin ligase complex through its constitutively phosphorylated DS52GXXS56 motif. In this process, Vpu was found to escape degradation, while inhibiting the degradation of βTrCP natural targets such as β-catenin and IκBα. We further addressed this Vpu inhibitory funct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
50
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(55 citation statements)
references
References 47 publications
5
50
0
Order By: Relevance
“…This would make Vpu itself a likely target for SCF-dependent ubiquitination and turnover. However, it has also been reported that WT Vpu is as stable as Vpu2/6 (16), that Vpu is a stable, competitive inhibitor of ␤TrCP (13), that Vpu is degraded in a ␤TrCP-independent manner (14), that Vpu is degraded by the lysosome (15), and that Vpu is both polyubiquitinated in a ␤TrCP-dependent mechanism and degraded by the proteasome (12). Curiously, among the reports of Vpu stability, they also show direct evidence that Vpu2/6 is more stable that WT Vpu (70), suggesting that Vpu is in fact being turned over via a ␤TrCP-dependent mechanism.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This would make Vpu itself a likely target for SCF-dependent ubiquitination and turnover. However, it has also been reported that WT Vpu is as stable as Vpu2/6 (16), that Vpu is a stable, competitive inhibitor of ␤TrCP (13), that Vpu is degraded in a ␤TrCP-independent manner (14), that Vpu is degraded by the lysosome (15), and that Vpu is both polyubiquitinated in a ␤TrCP-dependent mechanism and degraded by the proteasome (12). Curiously, among the reports of Vpu stability, they also show direct evidence that Vpu2/6 is more stable that WT Vpu (70), suggesting that Vpu is in fact being turned over via a ␤TrCP-dependent mechanism.…”
Section: Discussionmentioning
confidence: 99%
“…CD4 is subsequently degraded by the proteasome (10) via what appears to be a noncanonical ER-associated degradation (ERAD) pathway (11). The fate of Vpu in this process is the subject of some debate, as it has been reported to either be exceptionally stable or to be ubiquitinated and degraded (12)(13)(14)(15)(16).…”
mentioning
confidence: 99%
“…4A). Two of these mutations, A11G and S61A, occurred in highly conserved, previously established Vpu sequence domains involved in BST-2 down-regulation (39,40). We assessed the phenotypic consequence of these treatment-associated mutations by mutagenizing NL4-3 Vpu sequences at these positions and measuring the BST-2 down-regulation capacity of these mutant alleles in a subgenomic in vitro model (41).…”
Section: Hiv-1 Hypermutation Is Correlated With Apobec3 Expression Dumentioning
confidence: 99%
“…␤-TrCP binds to Vpu after casein kinase II-mediated phosphorylation of Vpu residues 52 and 56 (48). Vpu has been shown to stabilize several ␤-TrCP substrates, including the adherens junction protein ␤-catenin, NF-B inhibitor IB␣ (nuclear factor B), ATF4 (activating transcription factor 4), and cdc25A (cell division cycle protein 25A) (5,20). However, other ␤-TrCP substrates, such as Emi-1 (early mitotic inhibitor-1), remain unaffected by Vpu (20).…”
mentioning
confidence: 99%
“…Vpu has been shown to stabilize several ␤-TrCP substrates, including the adherens junction protein ␤-catenin, NF-B inhibitor IB␣ (nuclear factor B), ATF4 (activating transcription factor 4), and cdc25A (cell division cycle protein 25A) (5,20). However, other ␤-TrCP substrates, such as Emi-1 (early mitotic inhibitor-1), remain unaffected by Vpu (20). Of note, Vpu binding to ␤-TrCP does not promote its own degradation, and in fact, Vpu is degraded through a ␤-TrCP-independent mechanism that depends on the phosphorylation of residue 61 (20).…”
mentioning
confidence: 99%